Enhancement of bubble transport in porous electrodes and catalysts - Scheel, Thomas; Malgaretti, Paolo; Harting, Jens (Journal of Chemical Physics, 2024)
We investigate the formation and transport of gas bubbles across a model porous electrode/catalyst using lattice Boltzmann simulations. This approach enables us to systematically examine the influence of a wide range of morphologies, flow velocities, and reaction rates on the efficiency of gas production. By exploring these parameters, we identify critical parameter combinations that significantly contribute to an enhanced yield of gas output. Our simulations reveal the existence of an optimal pore geometry for which the product output is maximized. Intriguingly, we also observe that lower flow velocities improve gas production by leveraging coalescence-induced bubble detachment from the electrode/catalyst.
CRIS-Team Scopus Importer:2024-05-24